1993
DOI: 10.1056/nejm199309093291101
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Year Trial of Oleic and Erucic Acids (“Lorenzo's Oil”) as Treatment for Adrenomyeloneuropathy

Abstract: In this open trial we found no evidence of a clinically relevant benefit from dietary treatment with oleic and erucic acids ("Lorenzo's oil") in patients with adrenomyeloneuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
81
0
2

Year Published

1995
1995
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(90 citation statements)
references
References 42 publications
5
81
0
2
Order By: Relevance
“…24 In recent years, several therapeutic approaches have been proposed for this disease, but their effectiveness is still a matter of debate. 2,3,14,25 Therefore, the assessment of this disease is very important in order to monitor the efficacy of treatment. Magnetic resonance imaging (MRI) usually reveals typical brain lesions in children; 16 a high percentage of brain MRI abnormalities has been found in AMN, 4 but many of the patients were in advanced stages of the disease and presented predominant signs of mental deterioration.…”
mentioning
confidence: 99%
“…24 In recent years, several therapeutic approaches have been proposed for this disease, but their effectiveness is still a matter of debate. 2,3,14,25 Therefore, the assessment of this disease is very important in order to monitor the efficacy of treatment. Magnetic resonance imaging (MRI) usually reveals typical brain lesions in children; 16 a high percentage of brain MRI abnormalities has been found in AMN, 4 but many of the patients were in advanced stages of the disease and presented predominant signs of mental deterioration.…”
mentioning
confidence: 99%
“…Various therapeutic approaches including a lipid diet combining the administration of glycerol trioleate and trierucate (Lorenzo's oil) (14)(15)(16) failed to modify the evolution of the cerebral lesions of ALD. Four years ago, we reported that bone marrow transplantation (BMT) can reverse demyelination, if performed at a relatively early stage of its development (17).…”
mentioning
confidence: 99%
“…It is known that a ketogenic diet acts to increase the VLCFA levels, while lowering the intake of fatty acids lowers their level (e.g. the use of Lorentzo oil in X-ALD) [1,15,18].…”
Section: Discussionmentioning
confidence: 99%